INTERPERSONAL RESOURCES IN ACADEMIC WRITING: DOMINANT CHOICES AND FUNCTIONS OF ATTITUDE, ENGAGEMENT AND GRADUATION (An Appraisal Analysis of Introduction Sections in Doctoral Theses) - Nugraheni Woro Puspandari, - (2019)
Interpersonal resource is widely believed to facilitate the writers to construct a solid argument achieved byarticulating positive and negative point of view, engaging with other voices, and raising or lowering the writers' argument. In line with its importance, this study attempts to investigate the utilization of attitude, engagement, and graduation and their functions in facilitating the writers to construct arguments in introduction section of doctoral theses in English Department at one University in Bandung. This study has been framed by appraisal theory as suggested by Martin & White (2005) and Hood (2004) to unpack how the writers use language to express value (attitude), to manage voices to whom values are attributed (engagement) and to manipulate degrees of values (graduation). This study also has been shaped by the theory of academic writing emphasizing on moves in introduction proposed by Paltridge&Starfield (2007) to investigate the deployment of interpersonal resources in all moves of introduction section.This study employed a qualitative case study as research design with thematic analysis as data analysis technique. The documents used as samples in this study were nine introduction sections written by doctoral students. The result of analysis reveals that, in terms of attitude, these texts follow the pattern of argumentative genre indicated by the dominant use of appreciation signaling a strong preference for evaluating process/product (appreciation) rather than judging human behavior (judgement) or expressing feeling (affect) in constructing argument. With respect to the deployment of engagement, this study notesthat academic texts tend to be interactive indicated by a preference to activate multi-voiced (heteroglossic) rather than a single voice (monoglossic). As for graduation, the dominant use of force rather than focus signifies a preference to manipulate resource of graduation to make forceful arguments. Moreover, concerning the functions of interpersonal resources in introduction sections, this study identifies the crucial functions of attitude to construct a sound argument as it fits to perform a function to persuade the reader that the topic is interesting. At this point, it can be noted that positive values of attitude hold crucial functions to show the centrality of the topic and to inform the significance of the study whereas the negative values of attitude can be used to indicate that the research area is problematic. In relation to the deployment of engagement, this study spotsthe important roles of monoglossicof factual assertion to provide information which requires no dialogic alternatives. Meanwhile, another type monoglossic of focal proposition is more appropriate to be used for communicating evaluative issues. In addition, this study notesthe important function of heteroglossicresource of entertain to construct an effective argument as it allows the writers to express claims with precision, caution, and modesty. Apart from that, results of analysis reveal that engagement is seemingly effective to increase the degree of validity of the argumentand to shape the writers' position in a particular academic dialogue. In terms of graduation, this study identifiesthat this resource is potentially effective to create a powerful argument asit can be used to amplify or to reduce the strength of the writers' argument;---Penelitianiniberupayauntukmengkajipenggunaan attitude, engagement dan graduation besertafungsinyaadasuatupendahuluandalamdisertasi di program studi Bahasa Inggris di sebuahuniversitas di Bandung. Penelitaninidibingkaimenggunakanteori appraisal seperti yang disarankanoleh Martin & White (2005; Martin & Rose, 2003; Hood, 2004) untukmengungkapbagaimanapenulismenggunakanujaran yang berkaitandenganpendapatpenulis(attitude), mengontrolargumenpenulisberkenaandengankepadasiapaargumentersebutditujukan (engagement) danmemanipulasitingkatkekuatan argument (graduation). Penelitianini juga menggunakanteoripenulisanakademik yang secarakhususmembahasaspekaspekdalampendahuluansepertiyang disarankanolehPaltridge&Starfield (2007; Bunton, 2002; Samraj, 2008) untukmembahaspenggunaanungkapan interpersonal dalampendahuluansebuahdisertasi. Penelitianinimerupakansebuahstudikasusdengankarakterkualitatif yang menggunakandoumensebagaiteknikanalisis. Dokumen yang diggunakansebagaisampeldalampenelitianiniadalahsembilanpendahulandalamdisertasi. Hasilpenelitianmenunjukkanbahwadalampenggunaan attitude, penuliscenderungmenggunakan appreciation yang kemudiandiikutiolehjudgement dan affect. Berkenaandenganpenggunaan engagement, hasilpenelitianmenunjukkanbahwapenuliscenderungmenggunakanheteroglossicdaripadamonoglossic. Sedangkandalampenggunaan graduation, hasilpenelitianmenunjukkanbahwa force lebihseringdigunakandaripada focus. Lebihjauhlagi, penelitianinimenunjukkanbahwa attitude berperanpentinguntukmemkonstruksi argument yang kuat. Dari hasilpenelitiandapatdilihatbahwaattitude ygbernilaipositifberperanpentinguntukmenunjukkankeunggulantopikpenelitian, meriviupenelitianterdahulu, danmengungkapkankegunaanpenelitian. Sementaraitu, attitude yangbernilainegatifdapatdigunakanuntukmengindikasikanmasalahdi dalamtopikpenelitiandan di tempatpenelitian. Berkenaandenganpenggunaan engagement, hasilanalisismenunjukkanbahwa factual assertion berperanpentingdalammenyampaikaninformasiygmensyaratkanketiadaan dialog antarapenulisdanpembacasepertimenyatakantujuanpenelitian, susunantesis, definisipenelitiandan juga informasi yang bersifatpasti. Sementaraitu, focal proposition lebihtepatdigunakanuntukmenyatakaninformasi yangmemungkinkanuntukdidiskusikan. Sementaraitu, penelitianini juga menemukanperananpenting entertain untukmengaturkekuatanklaim yang dibuatolehpenulis. Disampingitu, hasilpenelitian jugamenunjukkanbahwaperpaduanpenggunaanantara acknowledge dan endorse dapatdigunakanutukmengakomodasi voice penulis lain dan, disaat yang sama, menunjukkanposisipenulisdalam argument yang dibangun. Berkenaandenganpenggunaan graduation, penelitianinimenunjukkanbahwa graduation berperanpentingdalammenyesuaikanataumengatur argument penulis.